1997
DOI: 10.1093/emboj/16.10.2682
|View full text |Cite
|
Sign up to set email alerts
|

rqh1+, a fission yeast gene related to the Bloom's and Werner's syndrome genes, is required for reversible S phase arrest

Abstract: of nucleotides in the cell are known to block DNA Department of Genetics, Harvard Medical School, 200 Longwood elongation (Vassilev and Russev, 1984; Friedberg et al Hartwell, 1995;Longhese et al., 1996). Here we rqh1 mutants. rqh1 ⍣ , previously known as hus2 ⍣ , demonstrate that reversible S phase arrest also requires encodes a putative DNA helicase related to the Escherprotective functions that are distinct from cell cycle ichia coli RecQ helicase, with particular homology to checkpoint controls. the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
320
2
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(351 citation statements)
references
References 48 publications
28
320
2
1
Order By: Relevance
“…Even though the BLM gene and several mutations responsible for Bloom's syndrome have been identi®ed in the last 4 years, the physiological function of the gene product remains uncharacterized. In contrast, functional data for the BLM homologs Rqh1 in ®ssion yeast and Sgs1p in budding yeast, have become available that suggest a crucial role for these proteins during the cell cycle (Stewart et al, 1997;Murray et al, 1997;Frei and Gasser, 2000). These data have prompted us to investigate a regulation of BLM during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the BLM gene and several mutations responsible for Bloom's syndrome have been identi®ed in the last 4 years, the physiological function of the gene product remains uncharacterized. In contrast, functional data for the BLM homologs Rqh1 in ®ssion yeast and Sgs1p in budding yeast, have become available that suggest a crucial role for these proteins during the cell cycle (Stewart et al, 1997;Murray et al, 1997;Frei and Gasser, 2000). These data have prompted us to investigate a regulation of BLM during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The BLM protein has been identi®ed as a member in the DExH boxcontaining RecQ helicase subfamily (Ellis et al, 1995). Its primary sequence presents similarities with all known members in the RecQ subfamily, including Escherichia coli RecQ (Umezu et al, 1990), Saccharomyces cerevisiae Sgs1p (Ganglo et al, 1994;Watt et al, 1995), Schizosaccharomyces pombe Rqh1 (Stewart et al, 1997), Drosophila melanogaster DmBLM (Kusano et al, 1999), human RecQL (Puranam and Blackshear, 1994;Seki et al, 1994), human Wrn, the product of the Werner's syndrome gene (Yu et al, 1996) and the recently identi®ed human RecQ4 and RecQ5 proteins (Kitao et al, 1998). Chester et al (1998) developed a mouse model for the human Bloom's syndrome, and showed that mouse embryos homozygous for a targeted mutation in the murine Bloom's syndrome gene die by embryonic day 13.5, but little is known about function(s) of BLM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of HU in WS cells is interesting because the sensitivity to HU is one of the phenotypical hallmarks of the yeast mutants in the orthologs of WRN, sgs1 and Rqh1. In the RecQ yeast mutants the sensitivity to replication arrest, as induced by HU, results in hyperrecombination and in the formation of the "cut" mitotic phenotype (Stewart et al, 1997;Yamagata et al, 1998). Such a phenotype, resulting from unequal distribution of the genetic material between the two daughter cells, is also associated with mutations in the Rad genes, which are responsible of the checkpoint response (Enoch and Nurse, 1990).…”
Section: Hypersensitivity Of Ws Cells To Cpt and Humentioning
confidence: 99%
“…Furthermore, in yeast, the RecQlike proteins seem involved in suppression of hyperrecombination, S-phase checkpoint control, and correct DNA segregation (Gangloff et al, 1994, Watt et al, 1995Stewart et al, 1997;Davey et al, 1998;Yamagata et al, 1998;Frei and Gasser, 2000). Noteworthy, yeast mutants in such RecQ-like helicases are extremely sensitive to agents that cause replication arrest, such as hydroxyurea because of uncontrolled illegitimate recombinational events (Stewart et al, 1997;Yamagata et al, 1998). The observed sensitivity of WS cells to 4-nitroquinoline-1-oxide (Gebhart et al, 1988;Ogburn et al (Lebel and Leder, 1998;Poot et al, 1999;Pichierri et al, 2000).…”
mentioning
confidence: 99%